North Americanization of Latin America? Culture, Gender, and Nation in the Americas - König, Hans-Joachim; Rinke, Stefan (Historamericana, 2022)
This volume assembles an interdisciplinary set of important contributions to crucial aspects of North Americanization in Latin America. Addressing categories such as culture, gender, and nation the articles provide new approaches to the study of inter- and trans-American relations in the twentieth century.